The Impact of the Pro-Environmental Movement on Santri’s Emotional Management at the UPT Jatian Waste Laboratory, Annuqayah Lubangsa Islamic Boarding School - Ni'mah, Qismatun; Nurhidayati, Titin (JSP: Jurnal Studi Pesantren, 2025)
The pro-environment movement is one that is concerned with the environment. Within this movement, pesantren (Islamic boarding schools) serve as gathering places for young people known as santri (students). One issue faced by pesantren is their substantial contribution to waste. Therefore, environmentally-conscious pesantren have been established. Various issues arise from unhealthy environments; not only that, a healthy environment significantly impacts individuals, especially their emotions. If the environment is unclean, smelly, and dirty, the emotions that arise are typically negative. Hence, individuals must cultivate a mindset that promotes good behavior towards the environment and their surroundings. This study aims to uncover two aspects: First, the existence of the pro-environment movement at the UPT Jatian Waste Laboratory of Pondok Pesantren Annuqayah Lubangsa; second, the implications of the pro-environment movement at the UPT Jatian Waste Laboratory on the emotional management of santri at Pondok Pesantren Annuqayah Lubangsa. This is to understand the extent to which the pro-environment movement affects the emotional management of santri and to facilitate this goal, the researcher uses a case study method with two theories: Pro-Environmental Behavior Theory, which focuses on behavior aimed at environmental preservation, and Emotional Intelligence Theory, which detects the impact of the pro-environment movement. The study concludes that the pro-environment movement can be an alternative for creating environmentally-conscious pesantren and has the goal of raising santri awareness about the importance of environmental care. Several processes in environmental care include Reduce, Reuse, and Recycle. Consequently, santri become aware of the importance of environmental maintenance. The implementation of this movement involves several supporting and hindering factors. Hindering factors include resistance from santri who have not yet accepted the pro-environment movement, while supporting factors include santri who have accepted it and are able to manage and control their emotions, thereby increasing their creativity and enthusiasm to participate in pro-environment activities.